2019
DOI: 10.1002/pssr.201900415
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Electron Irradiation on Cesium Fluoride‐Free and Cesium Fluoride‐Treated Cu(In1−x,Gax)Se2 Solar Cells

Abstract: Herein, the effects of electron irradiation on cesium fluoride (CsF)‐free and CsF‐treated Cu(In1−x,Gax)Se2 (CIGS) solar cells with fluence from 1 × 1013 to 1 × 1017 cm−2 are investigated. Both CsF‐free and CsF‐treated CIGS solar cells exposed to fluence up to 3 × 1015 cm−2 show self‐healing properties, due to the soaking effect from electron bombardment. This feature indicates the robustness of CIGS solar cells for long‐term space explorations. On the other hand, electron irradiation with fluence above 1 × 101… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…[2] These highest power conversion efficiency and high radiation tolerance show good potential for space application. [3][4][5][6][7][8][9][10][11][12][13][14][15] Flight data demonstrate no degradation of Cu(In,Ga)Se 2 (CIGS) solar cell performance by proton irradiation and thermal annealing. [8] Kawakita et al suggested that CIGS thin-film solar cells do not degrade in space by proton from an application point of view owing to the moderate temperature (50 C) of solar paddles in geostationary orbit and minority carrier injection during regular operation.…”
mentioning
confidence: 99%
“…[2] These highest power conversion efficiency and high radiation tolerance show good potential for space application. [3][4][5][6][7][8][9][10][11][12][13][14][15] Flight data demonstrate no degradation of Cu(In,Ga)Se 2 (CIGS) solar cell performance by proton irradiation and thermal annealing. [8] Kawakita et al suggested that CIGS thin-film solar cells do not degrade in space by proton from an application point of view owing to the moderate temperature (50 C) of solar paddles in geostationary orbit and minority carrier injection during regular operation.…”
mentioning
confidence: 99%
“…Therefore, the obvious degradation of V OC may be caused by the elements diffusion at p–n heterojuction interface and/or CZTSSe bulk region. [ 34 ] The J SC reduction could also arose from the performance changes of ITO transparent conductive layer, as described by XRD results. The remaining factor of V OC , J SC , FF, and PCE as a function of the displacement damage fluences in Figure 4e also shows that V OC is responsible for a greater contribution of the reduction in efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…This helps analyze the number of defects and electrical properties of the CTS layer. The irradiation properties and degradation mechanisms of Si, 17,18) GaAs, 19,20) InP, 20,21) and CIGS [22][23][24][25][26][27] solar cells have been reported. Recently, the usage of nextgeneration solar cells, such as CZTS 28) and NiO, 29,30) has also been reported.…”
Section: Introductionmentioning
confidence: 99%